A fully polynomial-time approximation scheme for total completion time minimization on a single machine with DeJong's learning effect and an availability constraint. Issue 8 (2nd August 2020) - Bai, Mengzhuo; Zhao, Yufang
ABSTRACT: This article studies a single-machine scheduling problem with DeJong's effect and a machine availability constraint taking the total completion time as the objective function. Firstly, a fully polynomial-time approximation scheme (FPTAS) was given for the problem, and afterwards that FPTAS was extended for the single-machine scheduling problem with deteriorating jobs, DeJong's learning effect and a machine availability constraint.